قوانين حماية المال العام وتفعيلها في أعادة استرداد الحقوق العامة لقطاع المؤسسات الحكومية في سلطنة عمان : دراسة تحليلية - Rashid Salim Said Alsaaidi
This study aims to highlight the role of laws in Sultanate of Oman related to protecting and retrieving of public funds, restoration of public rights, explaining these rights to public institutions and how to apply the laws which protecting public funds. Therefore, this study is confined to address the application of these laws on the public institutions, and apply the laws which protecting public funds on all members of the community in order to maintain public funds in Oman. The study employed descriptive analytical and deductive approaches to achieve the objectives. The findings indicate that all employees working in the public institutions related to public funds should be experienced, trustworthy and free of any judicial precedents which are associated to misconduct, embezzlement and corruption. In addition, findings show that authorities should exchange experiences and methods with various countries to take advantage of their expertise and experience in the maintenance and enhancement of public funds. Educational authorities should promote the concept of protecting public funds to people in order to create an educated citizen that sets eyes to protect public funds. The concept should be clearly articulated in the national curriculum and academic disciplines.